The Effectiveness of Learning Method Drawing on The Development Visual Language of Children Picture 6-9 Years (Case Study Elementary School Bandung City) - Maya Purnama Sari; Dian Rinjani (IJCAS (International Journal of Creative and Arts Studies), 2021)
Abstract Drawing learning methods have the aim to develop children's creativity, both formal and informal schools. Observations made in elementary schools and creative studios have two different types of images, namely storytelling and patterned pictures. Some of the images look engineered, so they do not look typical of children's drawings. The purpose of this study was to determine the effectiveness of drawing learning methods in children aged 6-9 years in formal schools and the suitability of the drawing results in the development of the visual language of children's drawings. The study used a mixed-method, descriptive qualitative by collecting photos, videos, behavioral observations. Quantitative by way of tabulating visual language to analyze the picture has a scheme in accordance with the development of the visual language of children's drawings. The theory used is the theory of drawing learning methods and the theory of visual language. The research findings namely, the method of learning to draw free and correlated expressions is very effectively used, because it focuses the child on the process rather than the result. The results of drawings in two schools have results that are in accordance with the stages of the development of the visual language of children's drawings. The method can be used as a reference in learning in formal schools to develop children's creativity. The direct method is not appropriate to use at the elementary school level because it makes the results of children's drawings not in accordance with the language development scheme. Efektivitas Metode Pembelajaran Menggambar Terhadap Perkembangan Bahasa Rupa Gambar Anak Usia 6 – 9 Tahun (Studi Kasus Sekolah Dasar Kota Bandung) Abstrak Metode pembelajaran menggambar memiliki tujuan untuk mengembangakan kreativitas anak, baik sekolah formal maupun informal. Pengamatan yang dilakukan di sekolah dasar dan sanggar kreatif terdapat dua jenis gambar yang berbeda, yaitu gambar bercerita dan berpola. Beberapa gambar terlihat direkayasa, sehingga tidak tampak kekhasan gambar anak. Tujuan penelitian untuk mengetahui efektivitas metode pembelajaran menggambar pada anak usia 6-9 tahun di sekolah formal serta kesesuaian hasil gambar terhadap perkembangan bahasa rupa gambar anak. Penelitian menggunakan metode campuran, kualitatif desktiptif dengan mengumpulkan foto, video, observasi perilaku. Kuantitatif dengan cara tabulasi bahasa rupa untuk menganalisis gambar tersebut memiliki skema yang sesuai dengan perkembangan bahasa rupa gambar anak. Teori yang digunakan adalah teori metode pembelajaran menggambar dan teori bahasa rupa. Temuan penelitian yaitu, metode pembelajaran menggambar ekspresi bebas dan berkorelasi sangat efektif digunakan, karena memfokuskan anak pada proses bukan hasil akhir. Hasil gambar pada dua sekolah memiliki hasil yang sesuai dengan tahapan perkembangan bahasa rupa gambar anak. Metode tersebut dapat dijadikan acuan dalam pembelajaran di sekolah formal untuk mengembangkan kreativitas anak. Metode langsung kurang tepat digunakan pada tingkat sekolah dasar karena membuat hasil gambar anak tidak sesuai skema perkembangan bahasa rupa gambar anak.